2001
DOI: 10.1002/ep.670200116
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of pilot‐scale pervaporation systems for volatile organic compound removal from a surfactant enhanced aquifer remediation fluid I. Spiral wound membrane modules

Abstract: -trichloro e t h a n e (TCA) at 450 mg /L, and tetrachloroethylene (PCE) I N T R O D U C T I O NSoils contaminated with non-aqueous phase liquids (NAPLs), such as the chlorinated solvents trichloroethylene (TCE) and tetrachloroethylene (PCE), pose a major environmental dilemma. The development of efficient processes to remediate and recover these solvents from soils is of paramount importance. One such process involves flushing the contaminated soils, in situ, with surfactant solutions [1][2][3][4][5][6][7]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…region as well as the effect of this partitioning on pervaporation performance [6][7][8]10,11,[15][16][17][18][19][20][21][22][23]. In particular, the partitioning of 1,1,1-TCA, TCE, toluene, and PCE in Alfoterra145 solutions was previously reported by our group [20].…”
Section: Cf1010 Module Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…region as well as the effect of this partitioning on pervaporation performance [6][7][8]10,11,[15][16][17][18][19][20][21][22][23]. In particular, the partitioning of 1,1,1-TCA, TCE, toluene, and PCE in Alfoterra145 solutions was previously reported by our group [20].…”
Section: Cf1010 Module Resultsmentioning
confidence: 96%
“…The result of this phenomenon, often referred to as concentration polarization, is that the VOC mass transfer efficiency and VOC/water selectivity are greatly reduced relative to that afforded by the membrane alone. To further complicate matters, when pervaporation has been applied to the removal of VOCs from actual groundwater, fouling of the membrane modules has been observed [6][7][8][9]. While typical membrane fouling involves the blinding of the membrane surface, fouling in pervaporation systems treating groundwater has generally involved the blockage of liquid flow paths in the modules by oils and precipitant particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some disadvantages to the plate and frame module, such as its large size and low-packet density. Only few previous studies [31][32][33] have reported on the spiral-wound module for PV process. Compared with the plate and frame membrane module, the spiral-wound configuration allows for a large membrane area in a low-volume module and can become a less expensive alternative substitute.…”
Section: Introductionmentioning
confidence: 98%
“…A larger pilot-scale study using hollow fiber membranes is also of interest in the light of a recent pilotscale study of the performance of spiral-wound pervaporation modules [6]. Using 5000 gal of VOC-laden s u rfactant-enhanced aquifer remediation re c o v e re d solution (shipped from Hill Air Force Base, Layton, U T, via a tanker truck), pervaporation-based re m o v a l of VOCs was carried out in a pilot plant (EPA, T&E facility, Cincinnati, OH) having spiral-wound pervaporation modules at feed flow rates between 0.25 and 2 gpm.…”
mentioning
confidence: 99%
“…The major goals of the pilot-plant experiments reported here were the following: i) Identify the suitability of the hollow fiber membrane-based pervaporation process for the tre a tment of the SEAR fluid on a larger scale; ii) Generate preliminary data which can be used later to predict the perf o rmance of the process on a larger scale and can be beneficial to scale-up and design objectives; iii) Gain insights into the process for selecting p rocess parameters to enhance process eff i c a c y and performance. The pilot-plant investigation was carried out in four stages: a) study the perf o rmance of the hollow fiber modules using simulated surfactant-containing feed; b) study the short-term perf o rmance of the hollow fiber modules using real SEAR fluid re c o v e red fro m the Hill Air Force Base, Layton, UT (and employed in the pilot plant studies for spiral-wound modules [6]); c) study the extended-term performance of the hollow fiber modules for fixed operating conditions using the feed solution as in (b) above; and d) study the shell side performance of the hollow fiber modules. Experiments identified in stage (d) were carried out since all studies in stages (a), (b) and (c) were carried out with tube-side flow of the feed solution (the mode re c o mmended and studied in [4,5]).…”
mentioning
confidence: 99%